If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X(X + 4) = 14 Reorder the terms: 2X(4 + X) = 14 (4 * 2X + X * 2X) = 14 (8X + 2X2) = 14 Solving 8X + 2X2 = 14 Solving for variable 'X'. Reorder the terms: -14 + 8X + 2X2 = 14 + -14 Combine like terms: 14 + -14 = 0 -14 + 8X + 2X2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-7 + 4X + X2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-7 + 4X + X2)' equal to zero and attempt to solve: Simplifying -7 + 4X + X2 = 0 Solving -7 + 4X + X2 = 0 Begin completing the square. Move the constant term to the right: Add '7' to each side of the equation. -7 + 4X + 7 + X2 = 0 + 7 Reorder the terms: -7 + 7 + 4X + X2 = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 4X + X2 = 0 + 7 4X + X2 = 0 + 7 Combine like terms: 0 + 7 = 7 4X + X2 = 7 The X term is 4X. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4X + 4 + X2 = 7 + 4 Reorder the terms: 4 + 4X + X2 = 7 + 4 Combine like terms: 7 + 4 = 11 4 + 4X + X2 = 11 Factor a perfect square on the left side: (X + 2)(X + 2) = 11 Calculate the square root of the right side: 3.31662479 Break this problem into two subproblems by setting (X + 2) equal to 3.31662479 and -3.31662479.Subproblem 1
X + 2 = 3.31662479 Simplifying X + 2 = 3.31662479 Reorder the terms: 2 + X = 3.31662479 Solving 2 + X = 3.31662479 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + X = 3.31662479 + -2 Combine like terms: 2 + -2 = 0 0 + X = 3.31662479 + -2 X = 3.31662479 + -2 Combine like terms: 3.31662479 + -2 = 1.31662479 X = 1.31662479 Simplifying X = 1.31662479Subproblem 2
X + 2 = -3.31662479 Simplifying X + 2 = -3.31662479 Reorder the terms: 2 + X = -3.31662479 Solving 2 + X = -3.31662479 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + X = -3.31662479 + -2 Combine like terms: 2 + -2 = 0 0 + X = -3.31662479 + -2 X = -3.31662479 + -2 Combine like terms: -3.31662479 + -2 = -5.31662479 X = -5.31662479 Simplifying X = -5.31662479Solution
The solution to the problem is based on the solutions from the subproblems. X = {1.31662479, -5.31662479}Solution
X = {1.31662479, -5.31662479}
| 13x+51=90 | | 5=6v | | f(x)=lx-1l+4 | | 5x+5=8x-13 | | -14-3n=5n-6n | | 5.61-8.94=3.76m+4.86 | | 5(w+2)=4(w+1) | | 13x+167=180 | | 6x-5x+4=-6 | | w=3(x+y+z)y | | v-16=-6 | | 3c-36=-3c-12 | | 9y-5y+10=-19 | | 0.33-4=-8 | | 2=5w+12 | | 5s-21=39 | | m=6(p+q)q | | 3(x+2)=-5-2(x-4) | | 25-39=11 | | 6X+19X-7=5(5X+5) | | -0.75=-0.6+s | | -2.4x=-2.88 | | 5x+28(x-2)=406 | | x-5x=7x-9x-x | | X+0.375=-1.75 | | -328=-56b+7 | | -5+4r=-5r+4r | | 19-13p=-5-17p | | 0.5+0.5j=0 | | ln(5X+1)=4.5 | | 3x+12=7x-22 | | x+3(x-3)=91 |